2018
DOI: 10.21107/jk.v11i2.4335
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Mild Steel in Seawater from Karangsong & Eretan of West Java Region, Indonesia

Abstract: <p><em>The corrosion behavior of mild carbon steel, has been investigated using an immersion test and energy-dispersive X-ray spectroscopy in solutions from the sites of Karangsong and Eretan, Northern Coast of West Java Region, Indonesia. As reference, solutions of 3.5% and 5% NaCl were prepared. Salinity, conductivity, and total dissolved solids (TDS) were measured. It was found that uniform corrosion observed on mild steel during the immersion test. Corrosion resistance of alloys decreases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Where CR = Corrosion rate in mills per year (mpy); ∆W = Weight loss in grams; K = Constant; d = metal density in g/cm 3 ; t = exposure time (day). The morphology of corroded surface, the distribution of elemental composition for rust product and various phase of corrosion products were identified by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD), respectively.…”
Section: Characterization and Analysis Of Corroded Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Where CR = Corrosion rate in mills per year (mpy); ∆W = Weight loss in grams; K = Constant; d = metal density in g/cm 3 ; t = exposure time (day). The morphology of corroded surface, the distribution of elemental composition for rust product and various phase of corrosion products were identified by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD), respectively.…”
Section: Characterization and Analysis Of Corroded Specimensmentioning
confidence: 99%
“…Moreover, the effect of pollutants, such as chloride and sulfur can enhance significantly the corrosion attack [2]. Sundjono et al [3] and Priyotomo et al [4] showed the detrimental effect of chloride with the increase of corrosion attack on carbon steel as represent of offshore structure. Furthermore, in the Atmospheric Corrosion of Carbon Steel after Short Exposure Gadang PRIYOTOMO et al http://wjst.wu.ac.th marine atmosphere, the main role of chloride refers to the atmospheric salinity.…”
Section: Introductionmentioning
confidence: 99%
“…The airborne salt that contains chloride ion was dissolved in a thin electrolyte layer on the metallic surface during the condensation process, where the conductivity of it increases significantly. The higher conductivity of electrolytes could contribute to accelerating the corrosion process of metals [18][19]. In current work, the airborne salinity level was represented by the deposition rate of chloride refers to International Standard Organization (ISO) 9223:2012 [20].…”
Section: Corrosion Rates Of Metalsmentioning
confidence: 99%
“…Penelitian ini menggunakan lapisan cat organic berbahan dasar akrilik sebagai binder. Cat berbasis akrilik merupakan cat kering cepat dimana pengikatnya merupakan senyawa polimer gugus akrilik [12]. Umumnya, cat berbasis akrilik ini dapat larut dalam media air (water borne acrylic) namun cat ini bersifat tahan air saat kering di udara terbuka.…”
Section: Pendahuluanunclassified
“…Namun, fenomena retak lapisan juga terjadi saat pengaplikasian. Retak lapisan akrilik yang menembus hingga logam dasar dapat terjadi dan diperparah dengan kondisi lingkungan garam sodium klorida (NaCl) dan berkelembaban diatas 80% [16].…”
Section: Hasil Dan Pembahasanunclassified